Neuroendocrine tumor of the ampulla of Vater treated with endoscopic papillectomy: A case report - Koichi Hamada; Atsushi Irisawa; Yoshinori Horikawa; Yoshiki Shiwa; Kae Techigawara; Masafumi Ishikawa; Takayuki Nagahashi; Daizo Fukushima; Noriyuki Nishino; Hideo Sakuma; Michitaka Honda (DEN Open, 2023)
Abstract We report the case of a 62‐year‐old female with a 6.3‐mm low‐grade neuroendocrine tumor of the ampulla of Vater, who underwent an endoscopic papillectomy. An endoscopic papillectomy was performed without complications. In the 26 months of follow‐up, no local recurrence or metastasis occurred. Endoscopic treatment of ampullary neuroendocrine tumors is controversial. However, endoscopic papillectomy may be considered a treatment option if neuroendocrine tumors are small (<10 mm), have a low grade (G1), or do not have muscle layer or bile duct invasion.